P102 Outcomes of coronavirus disease 2019 among patients with inflammatory bowel diseases and the influence of IBD-related medications– A Danish prospective population-based cohort study. (27th May 2021) - Attauabi, M; Poulsen, A; Kajbæk Verner-Andersen, M; Rosager Hansen, M; Pedersen, N; Pilegaard Prahm, A; Berg Lødrup, A; Haderselv, K; Larsen, L; Jess, T; Glerup, H; Molazahi, A; et al.
Abstract: Background: Population-based data regarding outcomes of coronavirus disease 2019 (COVID-19) among patients with ulcerative colitis (UC) and Crohn's disease (CD) are limited. Studies on the association of COVID-19 outcomes and immunomodulating therapies, are scarce. Therefore, we aimed to conduct a population-based study investigating the outcomes of COVID-19 among patients with UC and CD in Denmark. Methods: The Danish COVID-19 IBD Database is an extensive population-based database that prospectively monitors the disease course of laboratory-confirmed COVID-19 among patients with UC and CD in Denmark. Severe COVID-19 was defined as COVID-19 necessitating intensive care unit admission, ventilator use, or death. Regression analysis was adjusted for age, sex, disease type, disease activity, cardiovascular disease, and corticosteroids. Results: The study recruited 363 patients (UC: 223; CD: 140) from January 28 th, 2020, to February 7 th, 2021. A total of 36 (16.1%) and 18 (12.9%) patients with UC and CD, respectively, required a COVID-19 related hospitalization, while eight (3.6%) and three (2.1%) patients required intensive care treatment. Death due to COVID-19 was observed among eight (3.6%) and two (1.4%) patients, respectively. The association between these outcomes and IBD-related treatment is presented in Table 1. As shown, none of the IBD-related medications were associated with severe COVID-19 in univariate and adjusted analysis. However, systemic steroids were found to be associated with the risk of COVID-19 related hospital admission among patients with UC (adjusted odds ratio (aOR)=6.54 (95% CI 1.09-36.39)) and CD (aOR=5.45 (95% CI 2.07-12.24)). Conclusion: This ongoing Danish population-based study on COVID-19 outcomes among patients with UC and CD demonstrated severe COVID-19 among only a minority of patients, which was not associated with IBD-related medications. However, use of systemic steroids were associated with COVID-19 necessitating hospital admission among patients with UC and CD.